A Correlational Study on the Students’ Quranic Memorization and Their English Vocabulary Retention - Muhassin, Mohammad; Afifah, Khusnun; Hidayati, Dewi Ayu (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
This study aims to know whether there is a correlation between students’ Quranic memorization and their English vocabulary retention. This study chose 28 of seventh graders at Islamic Junior High School Az-Zahra Lampung in 2018/2019 academic year as the sample by means of cluster random sampling technique. This study applied correlational research design. The documented data of Quranic memorization of learners and the English vocabulary preservation were collected from the test and then analyzed for hypothetical testing employing Pearson's Product Moment equation. The outcome of the hypothetical test shows that Sig. (value) was generated by the value of significance = 0.000 < α = 0.05. It means the acceptance of Ha and the rejection of H0. Furthermore, based on the r value interpretation table, it is known that the observed r is a high correlation as the value of observed r is 0.622 in the 0.600 – 0.800 level. It can therefore be inferred that there is a significant correlation between the Quranic memorization of learners and the acquisition of English vocabulary.